2015
DOI: 10.1016/j.ijdevneu.2015.04.350
|View full text |Cite
|
Sign up to set email alerts
|

Study of the serum levels of polyunsaturated fatty acids and the expression of related liver metabolic enzymes in a rat valproate‐induced autism model

Abstract: To investigate whether the decreased level of serum polyunsaturated fatty acids (PUFAs) in patients with autism is associated with the expression of related liver metabolic enzymes, we selected rats that were exposed to valproic acid (VPA) on embryonic day 12.5 (E12.5) as a model of autism. We observed the serum levels of PUFAs and the expression of related liver metabolic enzymes, including Δ5-desaturase, Δ6-desaturase and elongase (Elovl2), in VPA-exposed and control rats on postnatal day 35 (PND35) and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The sex of the rodents influences behavioural outcomes in studies that consisted of both males and females. VPA exposure appeared to have no effect or a lesser effect in females [36][37][38][39][40], indicating females possess some resistance to social impairment induced by VPA, as opposed to males [41].…”
Section: Object-conspecific Testsmentioning
confidence: 87%
“…The sex of the rodents influences behavioural outcomes in studies that consisted of both males and females. VPA exposure appeared to have no effect or a lesser effect in females [36][37][38][39][40], indicating females possess some resistance to social impairment induced by VPA, as opposed to males [41].…”
Section: Object-conspecific Testsmentioning
confidence: 87%
“…Then, the following animal experiments, we strictly controlled dietary conditions in both groups in order to reduce the effects of dietary factors, and we still found that serum n-3 and n-6 PUFA levels were lower in ASD model rats relative to controls. Moreover, we observed that the expression of rate-limiting PUFA metabolic enzymes was downregulated in the ASD group [18]. However, genetic mutations were not taken into consideration in our previous work.…”
Section: Discussionmentioning
confidence: 99%
“…FADS1/2 and ELOVL2 gene polymorphisms may be the primary determinants not only of LC-PUFA status, but also of the biological effects exerted by LC-PUFAs [9]. We previously reported that serum LC-PUFA levels and delta-6 and -5 desaturase and elongase 2 were downregulated in a rat model of ASD relative to control rats under the same dietary conditions [18]. These findings indicate that mutations in the FADS1/2 and ELOVL2 genes resulting in abnormal expression of delta-6 and -5 desaturase and elongase 2, possibly due to perturbed LC-PUFA status during critical stages of neural development that increases susceptibility to ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the enhancement of eCB signal could promote the formation of LTD, and rescue the lack of eCB-mediated LTD in two types of monogenetic model of ASD mice [7]. Intriguingly, studies from our laboratory previously reported lower n-3 PUFAs levels were in autistic children, as well as in valproic acid (VPA)-induced rats [8,9], and the expressions of rate-limiting PUFA metabolic enzymes were downregulated in the VPA rats [8]. Afterwards, both prenatal and postnatal n-3 PUFA supplementation could markedly improve the learning and memory de cits of offspring [10].…”
Section: Introductionmentioning
confidence: 95%